(untitled) (Journal of the College of Education for Women, 2019)
This study examines the validity of e-poetry as an acceptable literary genre. Thethematic, stylistic and esthetic features of a selected number of e-poems produced bypoetry generators are analyzed for this purpose. The e-poems are then compared with anumber of works written by Dada poets in order to establish the literary merit of theformer.